Development of Humanized Mice in the Age of Genome Editing. Issue 10 (15th May 2017) - Hosur, Vishnu; Low, Benjamin E.; Avery, Cindy; Shultz, Leonard D.; Wiles, Michael V.
ABSTRACT: Mice are the most commonly used model organisms to study human disease. Many genetic human diseases can be recapitulated by modifying the mouse genome allowing the testing of existing and novel therapeutics, including combinatorial therapeutics, without putting humans at risk. Specifically, the development of "humanized" mice, that is, severely immunodeficient mice engrafted with functional human hematopoietic and immune cells and tissues, has revolutionized our ability to study and model human diseases in preclinical in vivo systems. Until recently it has been challenging to develop strains of humanized mice with targeted mutations or that transgenically express human genes with site‐specific mutations, and can permit optimal growth of functional human cells and tissues. However, recent advances in targeted nuclease‐based genetic engineering have enabled precise modification and development of humanized mouse models at an unprecedented pace. These modifications permit optimal growth of functional human cells and tissues and can be used to replicate human genetically determined diseases. J. Cell. Biochem. 118: 3043–3048, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Immunodeficient NSG mice, when engrafted with a human immune system, resulting in what are commonly known as humanized mice are replacing non‐human primates for the study of human diseases. Until recently it has been challenging to modify the genomes of humanized NSG mice; however, the availability of site‐specific nucleases and recombinases is enabling the development of next‐generation humanized mice to progress at an unparalleled pace.